Rural Households' Behaviour towards Modern Energy Technology Adoption Choices in East Gojjam Zone of Ethiopia: A Multivariate Probit Regression Analysis. Issue 1 (31st December 2023) - Chekol, Fasika; Giera, Mengistie; Alemu, Bizuayehu; Dessie, Molla; Alemayehu, Yirsie; Ewuinetu, Yeshiwas
Abstract: Many rural communities in developing countries continue to rely on biomass for energy, which has a negative impact on their socioeconomic development. Following the United Nation's Sustainable Development Goals—zero hunger and affordable modern/clean energy for all—many developing nations are now taking substantial initiatives to enhance rural clean energy access. As a result, this research explored rural household behaviors toward adopting alternative modern energy sources in East Gojjam Zone, Ethiopia. In an attempt to do so, 317 rural households were surveyed, and the data were analyzed using the multivariate probit (MVP) model. According to the MVP model results, education level, land size, credit availability, awareness, distance to market, and early neighbor adopters have positive effects on the choice of solar energy sources, whereas livestock holding, household income, extension contact, distance to biomass sources, and training access have negative effects. Besides this, the estimated MVP for improved cook stoves is positively influenced by livestock holding, income, extension contact, distance to biomass sources, awareness, training access, and early adopters. In contrast, education level, household size, agricultural experience, land size, access to credit, and distance to market all have a negative influence. Moreover, extension contact, distance to biomass sources, and availability of training have a positive impact on the choice of biogas energy sources, whereas credit access, awareness, distance to market, and early adopters have a negative effect. Regarding the propensity to use modern energy sources in the study area, infrastructural development was identified as critical.